Physical Activity Status of Elementary School Children in Bushehr in 1398 - M Shami (مجله اپیدمیولوژی ایران, 2021)
Background and Objectives: Physical activity is one of the most important components of life. The aim of this study was to evaluate the physical activity level of primary school students in Bushehr in 1398.